Dosimetry for nonuniform activity distributions: A method for the calculation of 3D absorbed‐dose distribution without the use of voxel S‐values, point kernels, or Monte Carlo simulations. Issue 4 (20th March 2013) - Traino, A. C.; Marcatili, S.; Avigo, C.; Sollini, M.; Erba, P. A.; Mariani, G.
Abstract : Purpose: : Nonuniform activity within the target lesions and the critical organs constitutes an important limitation for dosimetric estimates in patients treated with tumor‐seeking radiopharmaceuticals. The tumor control probability and the normal tissue complication probability are affected by the distribution of the radionuclide in the treated organ/tissue. In this paper, a straightforward method for calculating the absorbed dose at the voxel level is described. This new method takes into account a nonuniform activity distribution in the target/organ. Methods: : The new method is based on the macroscopic S ‐values (i.e., the S ‐values calculated for the various organs, as defined in the MIRD approach), on the definition of the number of voxels, and on the raw‐count 3D array, corrected for attenuation, scatter, and collimator resolution, in the lesion/organ considered. Starting from these parameters, the only mathematical operation required is to multiply the 3D array by a scalar value, thus avoiding all the complex operations involving the 3D arrays. Results: : A comparison with the MIRD approach, fully described in the MIRD Pamphlet No. 17, using S ‐values at the voxel level, showed a good agreement between the two methods for 131 I and for 90 Y. Conclusions: : Voxel dosimetry is becoming more and more important when performing therapy with tumor‐seeking radiopharmaceuticals. The method presented here does not require calculating the S ‐values at the voxel level, and thus bypasses the mathematical problems linked to the convolution of 3D arrays and to the voxel size. In the paper, the results obtained with this new simplified method as well as the possibility of using it for other radionuclides commonly employed in therapy are discussed. The possibility of using the correct density value of the tissue/organs involved is also discussed.